ASSESSMENT AND SURGICAL MANAGEMENT OF APPENDICITIS IN PEDIATRICS - Filho , Danillo Gondim da Silva; Alexandrino , Daiana Bettanin de Melo; Junqueira , Júlia Ferreira; Almeida , Joaquim Adriano Antunes de; Silva, Guilherme Augusto Santana; Trigueiro , Ana Paula Mendes Macedo; Moreira, Caroline da Silva; Ribeiro , Gabriela de Freitas; Cavalcante , Thiago Arruda Prado; Poleto , Guilherme Guimarães de Paula; Dechichi , Renata de Paula Ribeiro; Pera, Ana Beatriz Ianovali; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Acute appendicitis is one of the most common surgical emergencies in childhood, requiring rapid assessment and intervention. The clinical and radiological characteristics of this condition may vary in children, presenting significant diagnostic challenges. Surgical management is essential to avoid serious complications, such as perforation and peritonitis. Considering the importance of an early and precise approach, the evaluation and surgical management of appendicitis in pediatrics have been the subject of studies and systematic reviews to optimize clinical practice. Objective: To analyze and synthesize recent studies on the evaluation and surgical management of appendicitis in children, aiming to identify the best diagnostic and therapeutic practices. Methodology: The review was carried out in accordance with PRISMA guidelines. The PubMed, Scielo and Web of Science databases were searched for articles published in the last 10 years. The descriptors used included "pediatric appendicitis", "diagnosis", "surgery", "management" and "evaluation". The inclusion criteria were original studies focusing on clinical evaluation, imaging diagnosis and surgical management in pediatric patients with acute appendicitis. Exclusion criteria were studies in languages other than English, Portuguese or Spanish, case reports and narrative reviews. Results: The results highlighted the importance of careful clinical evaluation, together with the use of imaging tests, such as ultrasound and computed tomography, in the diagnostic approach to appendicitis in children. In addition, several surgical strategies were discussed, including laparoscopy, and the role of pre- and postoperative antibiotic therapy. Factors such as age, clinical presentation and time elapsed since the onset of symptoms were considered when making surgical decisions. Conclusion: The systematic review highlights the importance of a multidisciplinary and individualized approach in the evaluation and surgical management of appendicitis in pediatrics. The evidence gathered provides support to improve clinical practices, aiming for an effective and safe approach in this specific context.